The Strategy of Power Politics of the Philippines in Facing China in the South China Sea Conflict - Imanuddin, Ahmad Fauzi; Sugito, Sugito (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2021)
The South China Sea conflict has involved many parties, including the Philippines. In defending one of the most strategic islands, the Spratly Islands, the Philippines has exerted its hard power by increasing its military power strategy. By engaging the Armed Forces of the Philippines (AFP) and working with the U.S., the Philippines can increase its military power. The prior studies have only explored how the dispute in SCS is caused by maritime growth, and some have found the effective way to solve the issue is from the liberal perspective. This study uses a power politics approach to the Philippines' strategy to defend the Spratly Islands and its surroundings in the South China Sea dispute. It analyzes the Philippines' interests in the Spratly islands. The research was conducted using qualitative methods through literature study, and the data were analyzed, then described to obtain a complete picture of the answers to the problems studied. This finding explores how the Philippines' defense strategy works and how it is generated. The results of this study indicate that the defense strategy in the Spratly Islands is generated by the national interests of the Philippines, especially in the economic field.